Summary and conclusions - Arcas N.; Arroyo López F.N.; Caballero J.; D'Andria R.; Fernández M.; Fernandez Escobar R.; Garrido A.; López-Miranda J.; Msallem M.; Parras M.; Rallo L.; Zanoli R. (Present and future of the Mediterranean olive sector, 2013)
Seminar conclusions.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)